Silver sulfide as Q‐switcher and mode‐locker in Erbium‐doped fiber laser cavity. Issue 1 (7th October 2022) - Ahmed, Norizan; Omar, Suziana; Jusoh, Zulzilawati; Rahman, Husna A.; Dimyati, Kaharudin; Apsari, Retna; Harun, Sulaiman W.
Abstract: A silver sulfide saturable absorber (SA) was successfully employed in an Erbium‐doped fiber laser (EDFL) cavity for short and ultrashort pulse generations. The Q‐switched laser was obtained with an operation wavelength of 1566 nm, pulse rate of 93.81 kHz, and pulse duration of 1.68 μs at a 187.04 mW pump. As the EDFL cavity was optimized for mode‐locking operation by adding 100 m long single mode fiber, a stable soliton pulse train operating at 1564 nm was realized with a constant repetition rate of 1.88 MHz and pulse duration of 3.01 ps. The good nonlinear characteristics of the SA make synergetic contributions to the generation of high‐performance Q‐switched and mode‐locked lasers.